2010, Nr. 7, Table of Contents - Archyvas, Žurnalo (Buhalterinės apskaitos teorija ir praktika, 2018)
Accounting theory and practice Kristina Rudžionienė, Accounting: a science or an art?, 9 Jonas Mackevičius, Vilius Savickas, The issue of management accounting content, 17 Accounting teaching methodology Rasa Subačienė, Daiva Raziūnienė, The analysis of process of revenue accounting in Lithuanian authors‘ textbooks, 28 Kostas Valužis, Necessary usage of uniform accounting model during the teaching process, 36 Vida Vitartaitė, Indrė Knyvienė, Applying the case study method in the course of accounting, 46 Training of accounting specialists Valentinas Bružauskas, Danutė Zinkevičienė, Suggestions for the improvement of financial – accounting undergraduates studies, 51 Ona Gudaitienė, Melanija Sinevičienė, The benefits of the final practice for the future accountants, 63 Beata Harasim, Concern in studying accounting in Poland, 72 Gintarė Jakštonytė, Lukas Giriūnas, Evaluation of an accountant‘s professional skills and abilities, 76 Kristina Kundelienė, Lina Dagilienė, Vytautas Boguslauskas, Topicality of accounting specialists training at Kaunas university of technology, 83 Deimantė Kviklienė, Fausta Smolenskienė, Analysis of accounting subjects in the context of accounting study programme in case of Šiauliai state college, 91 Vaclovas Lakis, Transformation of accounting and auditing study at Vilnius university, 100 Romualdas Valkauskas, Developing the abilities of accounting specialists and theory of statistical conclusions, 113 Economical problems Edvardas Makšeckas, Auksė Makšeckienė, Relevance, need and quality assurance of training: agricultural education, 121 Sobotka Marcin, The effectiveness of innovative initiatives, 129 Tunkele Sigita, The production cost analysis of high value-added wood products in Latvia, 132